TAKE THE MOST OF THE STUDENTS' INPUT AND FEEDBACK TO PUSH A SUCCESSFUL LANGUAGE TEACHING - Anton Suratno (Soegijapranata Catholic University, 2001)
As we have recently observed that there has been a crucial change in most people's perception concerning approadch to teaching. As Nunan has recently mentioned that in current language teaching development, there has been a clear and observable gradual move from a top-down to getting more and more bottom-up approadch to the planning, implementation and evaluation of teaching and learning program. (Nunan, 1996: 129). He is supported by Gardner and Miller with their interest in learners autonomy (Gardner and Miller, 1996). also by Hutchison and Waters in their ESP learning-centred approach (Hutchison and Waters, 1993). There are some pratical reasons why student's input and feedback are likely to contribute to the success of the L-T programs. This article aims to put forward an overview of the stdents' potential contribution to the wat to aoptimize the learning and teaching processes by wat of considering the inportance of their regular input and feedback that they give to help plan, monitor and review or evaluate the TL programs. In other words, this paper will try to see a different perspective on achieving a good teaching program from the area beyong method of teaching.